Topical Analgesic Containing Methyl Salicylate and L-Menthol Accelerates Heat Loss During Skin Cooling for Exercise-Induced Hyperthermia - Wang, Gang; Zhang, Tingran; Wang, Anjie; Hurr, Chansol (Frontiers in Physiology, 2022)
Hyperthermia impairs physical performance and, when prolonged, results in heat stroke or other illnesses. While extensive research has investigated the effectiveness of various cooling strategies, including cold water immersion and ice-suit, there has been little work focused on overcoming the cutaneous vasoconstriction response to external cold stimulation, which can reduce the effectiveness of these treatments. Over-the-counter (OTC) topical analgesics have been utilized for the treatment of muscle pain for decades; however, to date no research has examined the possibility of taking advantage of their vasodilatory functions in the context of skin cooling. We tested whether an OTC analgesic cream containing 20% methyl salicylate and 6% L-menthol, known cutaneous vasodilators, applied to the skin during skin cooling accelerates heat loss in exercise-induced hyperthermia. Firstly, we found that cutaneous application of OTC topical analgesic cream can attenuate cold-induced vasoconstriction and enhance heat loss during local skin cooling. We also revealed that core body heat loss, as measured by an ingestible telemetry sensor, could be accelerated by cutaneous application of analgesic cream during ice-suit cooling in exercise-induced hyperthermia. A blunted blood pressure response was observed during cooling with the analgesic cream application. Given the safety profile and affordability of topical cutaneous analgesics containing vasodilatory agents, our results suggest that they can be an effective and practical tool for enhancing the cooling effects of skin cooling for hyperthermia.